Facial features associated with fear and happiness attract gaze during brief exposure without enhancing emotion recognition - Yu-Fang Yang; Matthias Gamer (Scientific Reports)
Abstract Facial features transmit emotions but their effect on visual orienting and explicit emotion recognition is debated. Here we examined whether fixating on diagnostic features of emotional expressions—such as eye region for fear and the mouth for happiness—affects saccadic targeting and improves recognition accuracy. Across two pre-registered experiments, participants viewed fearful, happy, and neutral faces for short intervals (50 or 150 ms) while the initial fixation location was manipulated. Although such brief stimulation does not allow for visual exploration, the faces still elicited reflexive saccades that occurred after stimulus offset. These saccades were modulated by the emotional expressions indicating a consistent preferential saccadic orienting towards diagnostic features, even with limited exposure. As this effect disappeared for inverted faces, it can be attributed to an extrafoveal processing of facial features instead of an attentional orienting towards physically salient image regions. Participants’ recognition accuracy was unaffected by the foveated facial feature, but this observation might also be due to ceiling effects in performance. Collectively, these findings contribute to understanding the attentional mechanisms of feature-based processing in the perception of emotional facial expressions.